RESOLUCIÓN DE PROBLEMAS Y ENSEÑANZA DE LAS CIENCIAS NATURALES - Jessup C., Margie N. Jessup C. (Tecné, Episteme y Didaxis: TED, 1998)
It has been wrongly cons,dered for a long time that resolving problems is a fundamental science activity. This activity is a characteristic when considering others human activities. Nevertheless, such activity constitutes an intrinsical element of human common life in ah spheres of his or her daily life and both individual and social life, it has gone into of the scientific field to be applied to anothers. This has been thought to be an expression of creative thinking. Due to it, since education in science different alternatives and approaches have been proposed. focusing in solving of problems like a process that con tributes to the appropriation of a scientific culture, that it is put at service of human being and it contributes well-being and of course, to elevate his or her qualty of life and of the groups it involves. Given the importance of the theme for education, in this paper it’s shown the Line of lnvestígation about solving problems in the frame of Doctorate in Education with emphasis in Education in Natural Science. Consequently, it presents succinctly the fundamental developings in the field, in order to point out the lineaments of this line of investigation.